Diseño de una estrategia sustentable para el estiércol porcino en la finca la Puente de la vereda aperche en el municipio de (Yacopí Cundinamarca) (2024)
This project focuses on the design of a sustainable strategy for the efficient management of swine manure on the La Puente farm located in Yacopí, Cundinamarca. Initially, a diagnosis was carried out by collecting data in the field and using the SWOT matrix, identifying problems such as inadequate management of manure, generation of odors, contamination by leachate and generation of greenhouse gases. Based on the analysis, the implementation of a hose-type tubular biodigester was selected as the ideal strategy, considering its capacity to process 30 kg of manure per day.